Nephrotic Syndrome as an Extramuscular Manifestation of Anti-EJ Antibody-Positive Dermatomyositis: A Case Report and Review of the Literature - Syoko Tsubouchi; Takahiro Mizuuchi; Yusuke Yamamoto; Daiki Fujimori; Kayo Ishii; Mayu Tago; Eri Kato; Hiroaki Mori; Haeru Hayashi; Koichiro Tahara; Tetsuji Sawada (Case Reports in Rheumatology)
Renal involvement is underestimated as an extramuscular manifestation of dermatomyositis (DM). Here, we describe a 67-year-old woman with anti-glycyl-transfer ribonucleic acid synthetase (anti-EJ) antibody and anti-ribonucleoprotein antibody-positive DM complicated by systemic sclerosis, who developed nephrotic syndrome concurrently with the exacerbation of DM, as indicated by incremental serum creatine kinase levels, high-intensity lesions on muscle magnetic resonance imaging, and active interstitial pneumonitis on chest computed tomography. Renal biopsy revealed the presence of immune-deposition in the glomerulus by immunofluorescence. To our knowledge, this is the first report describing the coexistence of anti-EJ antibody-positive DM and nephrotic syndrome. More reports of similar cases are warranted to substantiate the association.